Assessment of the quality of general movements in newborn infants: a tool to predict developmental disorders at an early age - Ahmad Suryawan; Bambang Permono; Komang Ayu Witarini; Risa Etika; Fatimah lndarso; Moersintowarti B. Narendra (Indonesian Pediatric Society Publishing House, 2016)
Background Nowadays, quality assessment of general movements (GMs) in infants can be used as a tool to predict developmental outcome. Until now, there is no published study in this field in Indonesia. Objectives The aim of this study was to evaluate the quality of GMs of newborn infants. Methods A prospective study was done at neonatal ward, Dr. Soetomo Hospital in Surabaya, between December 2006 and January 2007. A single supine position video recording of newborns at GMs preterm and writhing age was made using Precthl's method. Infants were chosen consecutively among singletons above 28 week gestational age. The quality of GMs was assessed by means of Gestalt perception by one of the authors, who had been trained and certified in GMs. GMs were classified into: normal-optimal, normal-suboptimal, mildly-abnormal, and definitely-abnormal. Correlation tests were used to assess the relationship between perinatal conditions and the quality of GMs. Results 106 videos were recorded, and 100 were assessed completely. Abnormal GMs were found in both 35 preterm age (normal-optimal 2.9%; normal-suboptimal 28.6%; mildly- abnormal45. 7o/o; definitely-abnormal22.9o/o) and 65 writhing age (3.1 o/o; 41.5%; 41.5%; 13.8%, respectively) (P=0.285). There was a weak negative correlation between birth weight and the quality ofGMs (r=-0.20, P=0.044). Conclusions The quality ofGMs in Indonesian newborn infants in our study was predominantly abnormal, which puts these infants at high risk for later developmental disorders. The lower the infants'birth weight, the more likely for abnormal GMs.